SPIRITUALITAS DAN MOTIVASI MENOLONG PADA MAHASISWA - Hendy Ginting (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
This study investigates the correlations between spirituality, the essential part of religion, and prosocial motive, the basis of prosocial and altruistic behavior. Participants of this study are 300 seminary students coming from various theological schools in Bandung. This study uses Hall & Edwards theoretical perspective on Self-God Relationship Awareness (ARG), Quality of one’s relationship with God (QRG), and four prosocial motives – egoism, collectivism, principleism, and altruism – of Daniel C. Batson. There is strong correlation between spiritual maturity and prosocial motives, C = 0,6364. ARG has significantly correlation with prosocial motives collectivism (rs = 0,417) and principleism (rs = 0,420). Therefore, Unstable (rs = 0,511) and Grandiose (rs = 0,511) sub dimensions related more with prosocial motives which driven by egoism. Realistic acceptance sub dimension is significantly related with prosocial motives altruism (rs = 0,422).